PENDEKATAN LOCATION QUOTIENT DAN SHIFT SHARE ANALYSIS DALAM PENENTUAN KOMODITAS UNGGULAN TANAMAN PANGAN DI KABUPATEN BANTUL - Mulyono, Joko; Munibah, Khursatul (Sekretariat Badan Penelitian dan Pengembangan Pertanian, 2016)
Land conversion causes competition in land use, and thus it is necessary to select leading commodities based on agro ecological zoning (AEZ). This study aimed to determine the leading commodities of food crops in Bantul Regency agro ecological zone. This study was conducted on March 2015. The data used was time series data of food crops harvested between 2008-2012 and agricultural commodities zone maps year 2013 based on AEZ with scale 1:50.000 obtained from the Statistics of Indonesia, Agriculture and Forestry Office, and AIAT. Commodities with comparative advantages were analysed by Location Quotient (LQ) while commodities with competitive advantages were analysed by Shift Share Analysis (SSA). Leading food crops commodities were determined through an overlay process using the ArcGIS software covering analysis results of LQ, SSA and agricultural commodities zone maps based on AEZ with scale 1:50.000. The result showed that the wetland paddy is a leading commodity in the study area. Based on comparative and competitive advantages, and compatibility with agricultural commodities zone based on AEZ, wetland paddy is the most leading commodity compared to corn, soybeans and peanuts. It is because of the distribution of this commodity in 10 districts (Sanden, Kretek, Pundong, Bambanglipuro, Pandak, Bantul, Jetis, Banguntapan, Kasihan, and Sedayu) with total area of 11,667 ha or 39.4% of agricultural land in Bantul Regency